Leitura e escrita: experiências teórico-metodológicas em sala de aula - FALABELO, Raimundo Nonato de Oliveira (Universidade Federal do Pará, 2020)
This articles intends to present a discursive view about the results of a research made with a first grade group of elementary school. Didactical and Cultural activities were developed in order to permit the exchange of experience, knowledge and wisdoms and enable interaction between the children who live in a reality of violence and exclusion of symbolic and corporeal property. According actions were happening, gradual changes were observed in the affective configuration in the classroom, provoking alterations and new ways of relationship of the children towards knowledge provided to them. It was observed that knowledge motivated children, making them see the links of affectionateness that are being produced in the relationships of learning. Getting aware of the learning, absorbing knowledge were actions that modified behaviors and attitudes of the children towards themselves, the teacher and their knowledge worked at school.